2023
DOI: 10.1007/s11031-023-10017-2
|View full text |Cite
|
Sign up to set email alerts
|

Coping with daily boredom: Exploring the relationships of job boredom, counterproductive work behavior, organizational citizenship behavior, and cognitive reappraisal

Abstract: Given that job boredom is experienced by more than half of the workforce on a daily basis, more scientific research on its potential outcomes and moderators is warranted. This study examined whether daily fluctuations in job boredom are associated with daily increases or decreases in counterproductive work behavior and organizational citizenship behavior, and whether individual differences in cognitive reappraisal moderated these relationships. Our hypotheses were tested in a daily diary study (396 daily obser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 96 publications
0
4
0
Order By: Relevance
“…Even though job boredom is considered as a transient and short-lived state and thus studies often focus on its immediate effects at the workplace, such as counterproductive work behaviours (e.g., Bruursema et al, 2011;Pindek et al, 2018;Spanouli et al, 2023;van Hooff & van Hooft, 2014), our results show that the effects of job boredom may extend beyond the workplace and be observed even after the workday ends.…”
Section: Discussionmentioning
confidence: 72%
“…Even though job boredom is considered as a transient and short-lived state and thus studies often focus on its immediate effects at the workplace, such as counterproductive work behaviours (e.g., Bruursema et al, 2011;Pindek et al, 2018;Spanouli et al, 2023;van Hooff & van Hooft, 2014), our results show that the effects of job boredom may extend beyond the workplace and be observed even after the workday ends.…”
Section: Discussionmentioning
confidence: 72%
“…Spector and Fox's (2002) model of voluntary work behaviors, for instance, posits that negative affect leads to CWB. Consistent with this notion, ndings from a daily diary study (Spanouli et al, 2023) demonstrated the lagged effect of job boredom on CWB at the within-person level. Thus, we expect job boredom to relate positively to next-day increases in CWB (Hypothesis 1).…”
Section: Introductionmentioning
confidence: 63%
“…CWBs are voluntary behaviors detrimental to the well-being of employees and the organization (Dalal et al, 2009). However, these studies primarily have been crosssectional and at the between-person level (for an exception, see Spanouli et al, 2023), failing to yield insight into within-person dynamics of job boredom and CWB. Consequently, research is unclear about the directionality of the job boredom-CWB relationship at the within-person level.…”
Section: Introductionmentioning
confidence: 99%
“…Lastly, Sypniewska (2020) stated that counterproductive work behavior is voluntarily acts presented by employees, whether they are conscious or not, that are harmful for the organization or its members. Spanouli et al (2023) termed counterproductive work behaviour as the 'dark side' of employees' performance that results in critical problems in organizations.…”
Section: Figurementioning
confidence: 99%